The electrochemical kinetic behaviour of nickel in acid aqueous solutions containing chloride and perchlorate ions - Piatti, Roberto C. V. (1969)
The electrochemical behaviour of polycrystalline nickel in acid solutions containing large excess either of NaCl or NaClO4 has been investigated, at potentials either more positive or negative than the rest potential of the metal. The electrode reactions were studied over a wide range of experimental conditions (pH, nickelous ion activity, temperature), and the influence of each variable on the experimental kinetic parameters has been determined